Kendala Penerapan Kawasan Tanpa Asap Rokok di Puskesmas Kedungbanteng Kabupaten Banyumas - Agoes Djatmiko; Haris Kusumawardana; Wahyu Hariadi (Wijayakusuma Law Review, 2025)
Kedungbanteng Community Health Center is one of the health service facilities in Banyumas Regency which should have implemented a 100% smoke-free area, but in reality, until now there are still visitors who smoke in the health center parking area, which shows that there is no compliance with the regulations set by the government. Based on Banyumas Regency Regional Regulation Number 26 of 2016 concerning Smoke-Free Areas, smoking is not permitted in areas that have been designated as smoke-free areas, including in health service facilities. The approach method used in this study is normative juridical, namely an approach that uses a positivistic legislative concept. The positivistic legislative concept is a written normative system created and promulgated by authorized officials and views law as an independent, closed, and separate normative system from real community life. The obstacle faced is the lack of knowledge and compliance from patients and the surrounding community or those who are accompanying patients to the Kedungbanteng Community Health Center that the health area is a Smoke-Free Area. It was directly found that there are still visitors to the Community Health Center who still smoke in the parking area. This is due to ignorance and the fact that the area is a no-smoking area. Furthermore, smoking has become a habit, often leading people to take the time to smoke while waiting.